1993
DOI: 10.1152/jappl.1993.75.5.1989
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function during dynamic exercise in untrained and moderately trained subjects

Abstract: The influence of exercise training on left ventricular function at rest (R), at anaerobic threshold (AT), and during peak exercise (PE) was evaluated in 12 healthy untrained and 13 trained (T) subjects who underwent Doppler echocardiography at R and radionuclide ventriculography at R and during exercise. The end-diastolic volume and stroke volume were significantly higher in the T group than in the untrained group at R. The ejection fraction rose significantly from R to AT and from AT to PE (80.0 +/- 0.84 vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 0 publications
2
15
0
5
Order By: Relevance
“…It is known that the aerobic fitness level is associated with low values of HRmax in healthy individuals, what has been related to high values of maximal cardiac output [29], high stroke volume and hypertrophy of the left ventricle [30]. This is in agreement with the findings of Fu et al [31], whom observed higher values of cardiac output after 12 weeks of aerobic training accompanied by an improvement in the OUES.…”
Section: Discussionsupporting
confidence: 86%
“…It is known that the aerobic fitness level is associated with low values of HRmax in healthy individuals, what has been related to high values of maximal cardiac output [29], high stroke volume and hypertrophy of the left ventricle [30]. This is in agreement with the findings of Fu et al [31], whom observed higher values of cardiac output after 12 weeks of aerobic training accompanied by an improvement in the OUES.…”
Section: Discussionsupporting
confidence: 86%
“…No presente estudo, no LA e no PCR a FC era de 115±14 e 156±18bpm, respectivamente, o que demonstra um aumento expressivo da FC, com o aumento da intensidade do exercício. Em estudo recente do nosso laboratório 30 , observamos que já no LA as velocidades de enchimento e de esvaziamento ventricular esquerdo aumentavam significativamente demonstrando que, a partir de um certo ponto do exercício, os períodos destinados às fases diastólica e sistólica são drasticamente reduzidos. Comportamento semelhante pode perfeitamente ter ocorrido entre os ciclos cardíacos, o que levaria a uma diminuição na VFC.…”
Section: Discussionunclassified
“…Ele teve por suposição que a prescrição de intensidade de exercício com base no LA ventilatório e no ponto de compensação respiratória seja a mais recomendada para se obter as adaptações benéficas na capacidade cardiopulmonar, verificada após um programa de condicionamento físico 2,11,12 . No entanto, nem o presente estudo, nem outros estudos na literatura compararam o efeito de programas de condicionamento físico prescritos pela forma direta e indireta.…”
Section: Discussionunclassified